2011
DOI: 10.3319/tao.2010.09.17.01(tibxs)
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of NINO3.4 SST and Inland Lake Level Variations Monitored with Satellite Altimetry: Case Studies of Lakes Hongze, Khanka, La-ang, Ulungur, Issyk-kul and Baikal

Abstract: Climate change can sometimes be reflected in variations in lake levels, thus understanding variations in lake levels and their relationship to climate change plays an important role in studying climate change. In this study, about 10 years of Topex/ Poseidon (T/P) altimetric data and 6 years of Jason-1 data were used to compute time series of level variations of six lakes in the Central and East Asia. The study sites were Hongze, La-ang, Ulungur, Khanka, Issyk-kul and Baikal Lakes. Time series of level variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…The relationships are reversed over the upper basin. Likewise, Guo et al [44] note that the Niño3.4 sea surface temperature has a lagged influence on the variation in lakes in East Asia. Here, we can observe that different archetypes are correlated with various Niño indices, suggesting that the extremal patterns are induced by different characteristics of the ENSO events.…”
Section: Discussion Of the Physical Mechanisms For Climate Teleconnecmentioning
confidence: 99%
“…The relationships are reversed over the upper basin. Likewise, Guo et al [44] note that the Niño3.4 sea surface temperature has a lagged influence on the variation in lakes in East Asia. Here, we can observe that different archetypes are correlated with various Niño indices, suggesting that the extremal patterns are induced by different characteristics of the ENSO events.…”
Section: Discussion Of the Physical Mechanisms For Climate Teleconnecmentioning
confidence: 99%
“…To study the periodic characteristics of sea level change in China seas and its vicinity, the 20-year SLA time series were analyzed with the wavelet analysis method (Guo et al, 2011), as shown in Figure 4. From Figure 4, we can find that there were two main cycles of sea level change over the China seas and its vicinity, which were 1 year and 9 years, respectively.…”
Section: Wavelet Analysis On Sea Level Changementioning
confidence: 99%
“…To date, the satellite radar altimeter and the tide gauge are the main techniques to collect SSHs (Fu and Cazenave, 2001;Guo et al, 2013). But SSHs at nadir can only be measured with the satellite altimeter and SSHs along coast line can be determined with the tide gauge point by point (Guo et al, 2011). More small spatial-temporal resolution of SSHs is needed to determine the mesoscale ocean currents and eddies.…”
Section: Introductionmentioning
confidence: 98%